How, when, and where information about breast cancer in Brazil is found using Google - Ohira, Nicole Mayumi Hafner; Gomes, Douglas Soltau (Mastology, 2021)
Introduction: This article sought to clarify the sources that women seek to find information about breast cancer. Methods: With a data collection from Google Trends, it was possible to list which keywords are most used when the population performs these searches and to know the volume of searches for the words “breast cancer” (câncer de mama ), “breast self-exam” (autoexame de mama), and “mammography” (mamografia) from 2009 to 2019. Results: In the search for “breast cancer” ( câncer de mama ), it was seen that the searches for “breast cancer” (câncer de mama ), “breast cancer symptoms” (câncer de mama sintomas ), “symptoms of breast cancer” (sintomas de câncer de mama ), “what is cancer of breast” (o que é câncer de mama ), and “types of breast cancer” (tipos de câncer de mama ) are the five most prevalent. Data were also displayed that reflect the importance of the awareness campaign for this type of cancer, the Pink October, since the months of October of the years in question were the ones that had the highest search volume for the keywords “cancer of breast” (câncer de mama), “breast self-examination” (autoexame de mama), and “mammography” (mamografia). In addition, it was noticed that many sites with a greater chance of getting hits due to their being in the first places in the survey did not have the name of the sources from which they had obtained their data and/or the names of the authors, and it was not possible to know the quality of the information published there. Conclusion: It is possible to notice the positive effect that the Pink October campaign has, which can contribute to a greater awareness of the importance of breast self- examination and mammography. In addition, it is necessary to be careful when looking for information in the online environment, since not all sites inform the source and/or the name of the author of the article.